2017
DOI: 10.1097/ccm.0000000000002254
|View full text |Cite
|
Sign up to set email alerts
|

Case Volume-Outcomes Associations Among Patients With Severe Sepsis Who Underwent Interhospital Transfer*

Abstract: Objective Case volume-outcome associations bolster arguments to regionalize severe sepsis care, an approach that may necessitate inter-hospital patient transfers. Although transferred patients may most closely reflect care processes involved with regionalization, associations between sepsis case volume and outcomes among transferred patients are unclear. We investigated case volume-outcome associations among patients with severe sepsis transferred from another hospital. Design Serial cross-sectional study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
0
21
1
Order By: Relevance
“…First, only 17% of Pennsylvania hospitals met our minimum volume threshold for inclusion in the study, reducing the number of hospitals that we were able to study. Although low case volumes themselves may be a marker of poor quality, the fact that no estimates could be made at 83% of Pennsylvania hospitals is concerning (31). Second, among those remaining, our hierarchical modeling approach, which is a standard approach to benchmarking (32), substantially shrunk the mortality rate toward the overall average.…”
Section: Discussionmentioning
confidence: 99%
“…First, only 17% of Pennsylvania hospitals met our minimum volume threshold for inclusion in the study, reducing the number of hospitals that we were able to study. Although low case volumes themselves may be a marker of poor quality, the fact that no estimates could be made at 83% of Pennsylvania hospitals is concerning (31). Second, among those remaining, our hierarchical modeling approach, which is a standard approach to benchmarking (32), substantially shrunk the mortality rate toward the overall average.…”
Section: Discussionmentioning
confidence: 99%
“…This fact is reinforced by observing that rural patients who bypass their local hospitals have 5.6% higher mortality than patients who were treated in rural hospitals, despite the fact that many were transferred. [7] In large-scale studies measuring the impact of hospital volume on survival, Ofoma et al showed that patients transferred to high-volume hospitals had better survival [12], but the impact of high-volume hospital care was not nearly as strong in transferred patients than in patients who presented to a high-volume hospital initially. [13] Interestingly, most of the benefit of being transferred to a higher volume hospital was observed in patients with the fewest organ failures [12], suggesting that a threshold may exist where even inter-hospital transfer cannot rescue patients from poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[7] In large-scale studies measuring the impact of hospital volume on survival, Ofoma et al showed that patients transferred to high-volume hospitals had better survival [12], but the impact of high-volume hospital care was not nearly as strong in transferred patients than in patients who presented to a high-volume hospital initially. [13] Interestingly, most of the benefit of being transferred to a higher volume hospital was observed in patients with the fewest organ failures [12], suggesting that a threshold may exist where even inter-hospital transfer cannot rescue patients from poor outcomes. We have previously observed that transferred patients have significantly lower adherence with Surviving Sepsis Campaign guidelines, suggesting that the timing of transfer and the care provided before transfer may be responsible for much of the outcome differences observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely care is associated with improved clinical outcome [56,130], and the conditions under which patients require sepsis care impair their ability to choose their setting for care (e.g., vulnerable population). Delays in sepsis recognition and transfer continue to put patients at risk [131]. While sepsis care does not require advanced technology, it does require staffing and procedural resources not available in all hospitals [132].…”
Section: Need For a Sepsis Regionalization Networkmentioning
confidence: 99%